Developmental delay in infants and toddlers with sickle cell disease: a systematic review. (17th September 2021) - Hoyt, Catherine R; Varughese, Taniya E; Erickson, Jeni; Haffner, Natalie; Luo, Lingzi; L'Hotta, Allison J; Yeager, Lauren; King, Allison A
Abstract : Aim: To summarize developmental delay among infants and toddlers with sickle cell disease (SCD). Method: This systematic review included studies that reported developmental outcomes of children with SCD between 0 months and 48 months of age and followed standards set forth by the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results: Ten studies were included, describing 596 unique developmental assessments. The rate of developmental delay ranged from 17.5% to 50% and increased with age. Cognition was the only domain included in all studies and the most frequently identified delay. One study reported that more severe SCD genotypes predicted worse development, while five studies reported no difference in rates of developmental delay across genotypes. Interpretation: These findings emphasize the need for standardized screening to identify children with SCD at risk of delay at a young age to facilitate appropriate referrals for therapeutic intervention. Frequent and comprehensive developmental screening is necessary among all SCD genotypes.